Obtaining precious metal from mining solid wastes - Romero Baylón, Alfonso (2009)
This study tell us about the recovery of precious metals like: gold and silver which are present in the mining tailing through the Hidrometallurgy Treatment such as the leaching by cyanidation in ponds, which is a method of curate that involves the use of cement for agglomerating the gold and in this way recovering values of gold and silver with the purpose of giving an aggregate value to the tailing. The study involves the initial chemical analysis of the three critical points of sampling in situ: P190, P192, P197, whose initials grades are: 0.514 gr/TC, 0987 gr/TC, 0.719 gr/TC respectively, that then there were subjected to the experimental tests of leaching by cyanidation with the purpose of obtaining the recovery of valuable metals of gold present in the three point above mentioned.